‘Weighing’ Losses and Gains: Evaluation of the Healthy Lifestyle Modification After Breast Cancer Pilot Program - Male, Dana; Fergus, Karen; Yufe, Shira (Frontiers in Psychology, 2022)
Objectives: Maintaining healthy weight is a common concern for breast cancer survivors (BCSs) given the association between increased adiposity and adverse health outcomes (e.g., poorer quality of life, increased risk of recurrence, mortality). This pilot study sought to develop and evaluate a novel online group-based intervention (Healthy Lifestyle Modification after Breast Cancer; HLM-ABC) to help BCSs make healthy lifestyle changes intended to yield not only beneficial physical outcomes (i.e., weight loss, reduced body mass index) but also greater behavioural (e.g., increased physical activity, healthier eating), and psychosocial well-being (e.g., self-efficacy, motivation, body image). Methods: An exploratory single-arm, mixed-method triangulation design was employed to evaluate the feasibility and preliminary effectiveness of the HLM-ABC intervention for overweight BCSs. Fourteen women participated in the 10-week intervention and completed quantitative measures of the above-mentioned outcomes at baseline, post-treatment, six-month, and 12-month follow-up time points. Qualitative data were obtained post-treatment via semi-structured interviews and a treatment satisfaction questionnaire. Results: Participants lost an average of 2.83% of their baseline weight (M = 196.65; SD = 38.59) by one-year follow-up (M=191.29; SD = 33.91), equal to a small effect size (d = -0.37). Despite achieving only modest weight loss, participants achieved meaningful gains in the form of increased physical activity (d = 0.2), discovery of gratifying movement, more intuitive eating habits (d = 1.12), greater bodily and emotional awareness, and positive shifts in beliefs about being able to make healthy choices regarding food (d = 0.63) and physical activity (d = 0.38). Furthermore, they demonstrated a slight improvement in body image (d = 0.36) and described feeling more self-compassionate, empowered, and acknowledging of variables beyond control (i.e., hormonal therapy, unsatisfactory surgery) that can present barriers to change. Conclusions: After completing a 10-week online program, participants achieved meaningful and lasting changes on a number of healthful indicators, even when this did not correspond with a significant reduction in weight. Findings highlight the complex, multifaceted nature of “health” and lend support for promotion of healthier lifestyle following cancer treatment that encompasses not only physical weight, but also behaviour, psychosocial well-being, and (often unmodifiable) circumstances such as life-preserving hormonal treatments.